Quality of Life Assessment Among Patients Living With Hepatosplenic Schistosomiasis and Schistosomal Myeloradiculopathy - Roriz, Silvana Júnia; Pereira, Thiago Almeida; Vaz de Melo Trindade, Guilherme; Caporali, Júlia Fonseca de Morais; Lambertucci, José Roberto (Frontiers in Medicine, 2021)
Schistosomiasis is a major public health problem in tropical areas of the world. Health-related quality of life (HRQOL) measurement is being widely used to evaluate the impact of a disease or treatment in several aspects of daily life. However, few studies evaluated the impact of severe forms of schistosomiasis on HRQOL of affected individuals and compared them to healthy controls with a similar socio-demographic background. Our aims were to evaluate the HRQOL in patients with hepatosplenic schistosomiasis (HS) and schistosomal myeloradiculopathy (SMR) and healthy volunteers (HV) and determine if clinical complications of the disease are associated with HRQOL scores. We interviewed and evaluated the HRQOL in 49 patients with HS, 22 patients with SMR, and 26 HV from an outpatient clinic of the Federal University of Minas Gerais University Hospital using the WHOQOL-BREF questionnaire. SMR and HS patients had a significantly lower overall quality of life score when comparing with the HV control group (p = 0.003 and p = 0.005, respectively). Multivariate ordinal regression model adjusted for sex, age, and educational level indicated that HS and SMR patients have three and five times more chances of having a lower quality of life than healthy volunteers (Odds Ratio 3.13 and 5.04, respectively). There was no association between complications of HS disease and quality of life scores. In contrast, worse quality of life was observed in SMR patients that presented back or leg pain, leg paresthesia, and bladder dysfunction. In conclusion, HS and SMR significantly impact the overall quality of life of the affected individuals, reinforcing the importance of efforts to control and eradicate this debilitating disease and suggesting that multidisciplinary clinical management of schistosomiasis patients would be more appropriate and could potentially improve patient's quality of life.